Electrolyte for magnesium ion battery and preparation method thereof
By using electrolytes of magnesium hexafluoroisopropoxyborate and organic ether solvents in magnesium ion batteries, and adding ionic compounds with anions different from anions in the solute as additives, the problem of insufficient storage performance of magnesium ion batteries under large currents is solved, and a high compatibility and rapid desolvation process is achieved, which significantly improves the electrochemical performance of magnesium ion batteries.
Patent Information
- Application Number
- CN202310041131.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-01-12
AI Technical Summary
The magnesium ion battery positive electrode material is insufficient in magnesium ion storage performance under large currents, resulting in a huge gap between actual performance and theoretical capacity.
An electrolyte prepared by magnesium hexafluoroisopropoxyborate (MgBHFIP) as a solute, an organic ether solvent and an ionic compound whose anions differ from anions in the solute are used as additives. This electrolyte promotes the desolvation process and has high compatibility with the positive electrode material.
The reversible discharge specific capacity of nano CuSe positive electrode materials under large currents has been significantly improved, which solves the problem of poor performance of magnesium ion battery positive electrode materials under large currents, and provides an important electrolyte solution for the development of high-power magnesium ion batteries.
Smart Images

Figure CN115832438B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium ion batteries, and in particular to an electrolyte used in magnesium ion batteries and a preparation method thereof. Background Art
[0002] Due to the limited lithium resources and uneven distribution in the earth's crust, the cost of metallic lithium has increased dramatically, so there is an urgent need to develop energy storage systems other than lithium to meet market demand. The theoretical specific capacity of magnesium metal as a negative electrode is 2205mAh / g (3833mAh / mL), the electrode potential is about -2.37V vs.SHE, and its mining cost is only about 1 / 24 of that of lithium. Rechargeable magnesium-ion batteries have been regarded as one of the most promising non-lithium energy storage technologies because they use multivalent magnesium metal negative electrodes with high capacity, high safety, high abundance and uniform deposition. Although the research on magnesium-ion batteries is still in its early stages compared with lithium-ion batteries, some breakthrough research progress has been made, including the construction of highly reversible electrode systems, the design of ether-based electrolytes for efficient magnesium deposition and reversible magnesium ion transport, and the development of magnesium storage cathode materials with high theoretical energy density. However, the key obstacle to the practical application of high-performance magnesium-ion batteries is the slow magnesium ion storage kinetics in the cathode materials, which leads to a huge gap between the performance of the cathode materials in actual tests and the theoretical capacity.
[0003] Copper selenide (such as CuSe, Cu2Se, Cu3Se2 and Cu 2-x Se) materials due to their metal ions and Se 2- The weak interaction between CuSe and CuSe and their good conductivity make them potential cathode materials with fast magnesium storage kinetics. In the initial study, the nano-sized CuSe cathode was 50 mA g -1 Approximately 200 mAh g -1 However, the performance of CuSe cathode at high current is very poor, which may be due to the large energy barrier for Mg-Cl bond breaking in chloride-containing electrolyte and the corrosive effect of chloride-containing electrolyte.
[0004] The use of chlorine-free electrolyte can avoid the corrosive effect of chlorine-containing electrolyte in magnesium-ion batteries, thereby significantly improving the high-current performance of nano-CuSe positive electrode materials. However, its reversible discharge specific capacity is still far lower than the theoretical capacity (376mAh / g), which cannot meet the high-current magnesium storage performance of the magnesium-ion battery positive electrode. Summary of the invention
[0005] The purpose of the present invention is to provide an electrolyte for magnesium ion batteries and a preparation method thereof in view of the deficiencies in the prior art. The electrolyte is prepared from a boron-based magnesium salt solute, an organic ether solvent and an additive. The electrolyte promotes the desolvation process and has high compatibility with positive electrode materials. The magnesium ion storage performance of the positive electrode material under high current is greatly improved.
[0006] A first aspect of the present invention provides an electrolyte for a magnesium ion battery, comprising a solute, a solvent and an additive; wherein the solute comprises magnesium hexafluoroisopropoxyborate, the additive comprises an ionic compound whose anions are different from the anions in the solute, and the solvent comprises an organic ether solvent.
[0007] In an alternative embodiment, the additive includes an ionic compound whose anion is trifluoromethanesulfonate, hexafluorophosphate, bistrifluoromethanesulfonimide, bisfluorosulfonimide, perchlorate or hexamethyldisilazide.
[0008] In an optional embodiment, the organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0009] In an optional embodiment, in the electrolyte, the concentration of magnesium hexafluoroisopropoxyborate is 0.05 to 0.5 mol / L.
[0010] In an optional embodiment, in the electrolyte, the concentration of the additive is 0.05 to 0.5 mol / L.
[0011] A second aspect of the present invention provides a method for preparing the electrolyte for magnesium ion battery, comprising the following steps:
[0012] Dispersing magnesium borohydride in a first organic ether solvent to obtain a magnesium borohydride dispersion, adding hexafluoroisopropanol to the magnesium borohydride dispersion under stirring conditions, and reacting under the protection of an inert atmosphere to obtain a mixed solution after the reaction is completed;
[0013] Under the protection of an inert atmosphere, the mixed solution is filtered, and the filtrate is vacuum-treated to remove the solvent to obtain magnesium hexafluoroisopropoxyborate;
[0014] Continuing under the protection of an inert atmosphere, magnesium hexafluoroisopropoxyborate and an additive are dissolved in a second organic ether solvent to obtain the desired electrolyte; wherein the additive is an ionic compound whose anion is different from the anion in the solute.
[0015] In an optional embodiment, the concentration of the magnesium borohydride dispersion is 10 to 50 g / L.
[0016] In an optional embodiment, the molar ratio of magnesium hexafluoroisopropoxyborate to magnesium borohydride is (4-6):1, and the molar ratio of magnesium hexafluoroisopropoxyborate to additive is 3:(1-5).
[0017] In an optional embodiment, the concentration of the additive is 0.05-0.5 mol / L, and the additive includes an ionic compound whose anion is trifluoromethanesulfonate, hexafluorophosphate, bistrifluoromethanesulfonyl imide, bisfluorosulfonyl imide, perchlorate or hexamethyldisilazide.
[0018] In an optional embodiment, the concentration of the magnesium hexafluoroisopropoxyborate is 0.05-0.5 mol / L.
[0019] In an alternative embodiment, the first organic ether solvent comprises a mixture of one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran and 2-methyltetrahydrofuran;
[0020] The second organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0021] A third aspect of the present invention provides a magnesium ion battery, wherein the electrolyte thereof adopts the electrolyte applied to the magnesium ion battery as mentioned above.
[0022] It can be seen from the above scheme that the electrolyte applied to magnesium ion batteries proposed by the present invention has the following significant advantages:
[0023] The electrolyte of the present invention adopts an organic ether solvent and magnesium hexafluoroisopropoxyborate (MgBHFIP) solute, and simultaneously adds an ionic compound whose anion is different from the anion in the solute as an additive. When the concentration of the solute magnesium salt is 0.3 mol / L, the solvent is ethylene glycol dimethyl ether, and the additive is 0.1-0.5 mol / L sodium trifluoromethanesulfonate, the conductivity is greater than 10 mS / cm, and the electrolyte has high ionic conductivity, excellent reversible magnesium deposition-dissolution performance, and high oxidation stability potential (>2.5 V vs. Mg / Mg 2+ , the working electrode is copper foil), which can be successfully applied to magnesium ion batteries.
[0024] In the electrolyte of the present invention, the introduction of anions in the additive changes the solvation structure of magnesium ions in the electrolyte, reduces the reaction energy barrier of desolvation, promotes the desolvation process, and further accelerates the charge transfer of the electrode reaction. The electrolyte has high compatibility with the positive electrode material, so that the positive electrode material has excellent reversible discharge specific capacity under high current. Therefore, when the electrolyte of the present invention is used for conversion reaction type positive electrode material, the magnesium ion storage performance of the positive electrode material under high current is greatly improved. The unique magnesium ion solvation structure makes the electrolyte of the present invention have important significance in the development of high voltage and high power magnesium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are the nuclear magnetic resonance (NMR) data of the powders obtained after the solvent in the electrolyte evaporates in Examples 1 and 3 of the present invention.
[0026] Figure 2 It is the laser Raman spectroscopy (Raman) data of the electrolyte in Example 1 and Example 3 of the present invention.
[0027] Figure 3 1 is the LSV curve of the electrolyte in Example 1 of the present invention on copper foil, aluminum foil and stainless steel.
[0028] Figure 4 1 is the LSV curve of the electrolyte in Example 2 of the present invention on copper foil, aluminum foil and stainless steel.
[0029] Figure 5 1 is the LSV curve of the electrolyte in Example 3 of the present invention on copper foil, aluminum foil and stainless steel.
[0030] Figure 6 1 is the LSV curve of the electrolyte in Example 4 of the present invention on copper foil, aluminum foil and stainless steel.
[0031] Figure 7 It is the magnesium deposition-dissolution curve of the Mg||Mg full battery assembled using the electrolyte in Example 3 of the present invention.
[0032] Figure 8 It is the AC impedance spectrum of the copper selenide positive electrode after standing in the electrolyte of Example 1 and Example 3 of the present invention for 10 hours.
[0033] Fig. 9 It is a graph of the cycle stability and coulombic efficiency of the copper selenide positive electrode at a current density of 100 mA / g in the electrolyte of Example 1 and Example 3 of the present invention.
[0034] Fig.10 The graphs are the cycle stability and coulombic efficiency of the copper selenide positive electrode at different current densities (200, 500, 1000 mA / g) in the electrolyte in Examples 1 and 3 of the present invention. DETAILED DESCRIPTION
[0035] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0036] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.
[0037] In order to improve the high-current magnesium storage performance of the positive electrode of a magnesium ion battery and promote the development of a high-power magnesium ion battery, the present invention provides an electrolyte that can be applied to a high-power magnesium ion battery and has a wide electrochemical stability window, high ionic conductivity, excellent reversible magnesium deposition characteristics and a rapid desolvation process.
[0038] In one embodiment of the present invention, an electrolyte for a magnesium ion battery is provided, comprising a solute, a solvent and an additive; wherein the solute comprises magnesium hexafluoroisopropoxyborate (MgBHFIP), the additive comprises an ionic compound whose anions are different from the anions in the solute, and the solvent comprises an organic ether solvent.
[0039] In an optional embodiment, the additive includes an anion of trifluoromethanesulfonate (OTf - ), hexafluorophosphate (PF6 - ), bis(trifluoromethanesulfonyl)imide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), perchlorate (ClO4 - ) or hexamethyldisilazide (HMDS - ) ionic compounds.
[0040] The anions in the above additives will interact with the magnesium ions, and the anions will participate in the solvation structure of the magnesium ions, changing the solvation structure of the magnesium ions. The solvation structure of the magnesium ions is [Mg(solvent) x ] 2+ becomes [Mg(solvent) m (anion) n ] + The introduction of anions lengthens the bond length between magnesium ions and solvents and weakens the interaction force, so this special magnesium ion solvation structure has a rapid desolvation process.
[0041] In an optional embodiment, the organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0042] The above solvent not only acts as a solvent to dissolve the organic magnesium salt, i.e. magnesium hexafluoroisopropoxyborate (MgBHFIP), but also coordinates with the organic magnesium salt to obtain a complexed magnesium cation through a complexed ether solvent. The process is as follows: after the organic magnesium salt is dissolved in the ether solvent, the magnesium salt is dissociated into magnesium cations complexed with the solvent [Mg(solvent) x ] 2+ (The amount of complexed solvent is related to the type of solvent) and anionic BHFIP - , where the complexed magnesium cation plays the role of transporting magnesium ions in the operation of magnesium ion batteries.
[0043] [Mg(solvent) x ] 2+ and [Mg(solvent) m (anion) n ] + , solvent refers to the solvent used in the electrolyte, and anion refers to the anion in the additive.
[0044] In an optional embodiment, in the electrolyte, the concentration of magnesium hexafluoroisopropoxyborate is 0.05 to 0.5 mol / L.
[0045] In an optional embodiment, in the electrolyte, the concentration of the additive is 0.05 to 0.5 mol / L.
[0046] In another embodiment of the present invention, a method for preparing the electrolyte for magnesium ion battery is provided, comprising the following steps:
[0047] Dispersing magnesium borohydride in a first organic ether solvent to obtain a magnesium borohydride dispersion, adding hexafluoroisopropanol to the magnesium borohydride dispersion under stirring conditions, and reacting under the protection of an inert atmosphere to obtain a mixed solution after the reaction is completed;
[0048] Under the protection of an inert atmosphere, the mixed solution is filtered, and the filtrate is vacuum-treated to remove the solvent to obtain magnesium hexafluoroisopropoxyborate;
[0049] Continuing under the protection of an inert atmosphere, magnesium hexafluoroisopropoxyborate and an additive are dissolved in a second organic ether solvent to obtain the desired electrolyte; wherein the additive is an ionic compound whose anion is different from the anion in the solute.
[0050] In an optional embodiment, the concentration of the magnesium borohydride dispersion is 10 to 50 g / L.
[0051] In an optional embodiment, the molar ratio of magnesium hexafluoroisopropoxyborate to magnesium borohydride is (4-6):1, and the molar ratio of magnesium hexafluoroisopropoxyborate to additive is 3:(1-5).
[0052] In an optional embodiment, the concentration of the additive is 0.05-0.5 mol / L, and the additive includes an ionic compound whose anion is trifluoromethanesulfonate, hexafluorophosphate, bistrifluoromethanesulfonyl imide, bisfluorosulfonyl imide, perchlorate or hexamethyldisilazide.
[0053] In an optional embodiment, the concentration of the magnesium hexafluoroisopropoxyborate is 0.05-0.5 mol / L.
[0054] In an alternative embodiment, the first organic ether solvent comprises a mixture of one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran and 2-methyltetrahydrofuran;
[0055] The second organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0056] In other embodiments of the present invention, a magnesium ion battery is provided, wherein the electrolyte thereof adopts the electrolyte previously applied to the magnesium ion battery, and the electrolyte has a wide electrochemical stability window, high ionic conductivity, excellent reversible magnesium deposition characteristics and a rapid desolvation process, and therefore, the magnesium ion battery has excellent electrochemical performance.
[0057] For better understanding, the present invention is further described below in conjunction with several specific examples, but the materials and processing techniques are not limited thereto, and the content of the present invention is not limited thereto.
[0058] Example 1
[0059] Comparative sample: No additives in the electrolyte
[0060] 0.8 g of magnesium borohydride and 50 mL of ethylene glycol dimethyl ether (DME) were added to a 100 mL round-bottom flask, and then 13 mL of hexafluoroisopropanol solution was slowly added dropwise under continuous magnetic stirring. After the addition was completed, stirring was continued for 12 hours under an argon atmosphere.
[0061] The reaction solution was then filtered under argon protection, and the ethylene glycol dimethyl ether (DME) solvent in the filtrate was removed by vacuum treatment to obtain magnesium hexafluoroisopropoxyborate solid (MgBHFIP).
[0062] In an argon atmosphere glove box, the solid was dissolved in ethylene glycol dimethyl ether to prepare a 0.3 M MgBHFIP / DME electrolyte.
[0063] Example 2
[0064] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.3M MgBHFIP+0.1MNaOTf / DME.
[0065] Example 3
[0066] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.3M MgBHFIP+0.3MNaOTf / DME.
[0067] Example 4
[0068] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.3M MgBHFIP+0.5MNaOTf / DME.
[0069] Example 5
[0070] The electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium hexafluorophosphate (NaPF6) as an additive, with a composition of 0.3M MgBHFIP+0.1MNaPF6 / DME.
[0071] Example 6
[0072] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium bistrifluoromethanesulfonimide (NaTFSI) as an additive, with a composition of 0.3M MgBHFIP+0.1MNaTFSI / DME.
[0073] Example 7
[0074] The electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium bis(fluorosulfonyl)imide (NaFSI) as an additive, and the composition was 0.3M MgBHFIP+0.1MNaFSI / DME.
[0075] Example 8
[0076] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, diethylene glycol dimethyl ether (DEGDME) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.3M MgBHFIP+0.3MNaOTf / DEGDME.
[0077] Example 9
[0078] The electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium perchlorate (NaClO4) as an additive, with a composition of 0.3M MgBHFIP+0.1MNaClO4 / DME.
[0079] Example 10
[0080] The electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased bis(hexamethyldisilazide) magnesium (Mg(HMDS)2) as an additive, and the composition was 0.3M MgBHFIP+0.1MMg(HMDS)2 / DME.
[0081] Embodiment 11
[0082] An electrolyte was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.1M MgBHFIP+0.1MNaOTf / DME.
[0083] Example 12
[0084] An electrolyte solution was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, tetrahydrofuran (THF) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.3M MgBHFIP+0.3M NaOTf / THF.
[0085] Example 13
[0086] An electrolyte solution was prepared using the MgBHFIP prepared in Example 1 as the electrolyte magnesium salt, tetrahydrofuran (THF) as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) as an additive, with a composition of 0.5M MgBHFIP+0.5M NaOTf / THF.
[0087] Embodiment 14
[0088] The MgBHFIP prepared in Example 1 was used as the electrolyte magnesium salt, ethylene glycol dimethyl ether (DME) and tetrahydrofuran (THF) in a volume ratio of 1:1 were used as the solvent, and commercially purchased sodium trifluoromethanesulfonate (NaOTf) was used as an additive to prepare an electrolyte with a composition of 0.3 M MgBHFIP + 0.3 M NaOTf / (DME + THF).
[0089] MRI test
[0090] The powder after the solvent of the electrolyte in Examples 1 and 3 was evaporated was subjected to nuclear magnetic resonance (NMR) test, and the results are as follows: Figure 1 shown.
[0091] NMR results show that after adding electrolyte magnesium salt MgBHFIP to the solvent DME (curve ii), the terminal -CH3 on DME, which is more sensitive to the shielding effect, undergoes a chemical shift to the high field direction, indicating that the Mg dissolved in DME 2+ According to the results of hydrogen spectrum area integration, the structure of magnesium ions in the electrolyte of Example 1 is [Mg(DME)3] 2+ .
[0092] After adding the electrolyte magnesium salt MgBHFIP and the additive NaOTf to the solvent DME (curve iii), the terminal group -CH3 on DME further shifts to the higher field direction, indicating that the interaction force between the cations in the mixed electrolyte and DME is stronger. According to the results of the hydrogen spectrum area integration, the cations (Mg 2+ and Na + ) together complexed 4 DME molecules.
[0093] Laser Raman spectroscopy test
[0094] Laser Raman spectroscopy was performed on the electrolytes in Examples 1 and 3. The results are as follows: Figure 2 shown.
[0095] Raman spectroscopy results show that after adding electrolyte magnesium salt MgBHFIP to solvent DME (curve ii), the peak representing the interaction between magnesium ions and DME appears at 878 cm -1This result corresponds to the NMR result. The structure of magnesium ions in the electrolyte in Example 1 is [Mg(DME)3] 2+ .
[0096] After adding electrolyte magnesium salt MgBHFIP and additive NaOTf to solvent DME (curve iii), the peak representing the interaction between magnesium ions and DME increases from 878 cm -1 Offset to 876cm -1 , indicating that the number of DME molecules interacting with magnesium ions has decreased. At the same time, the peak representing the interaction between sodium ions and DME appears at 866 cm -1 , magnesium ions and OTf - The peak of anion interaction appears at 1054 cm -1 and 766cm -1 . Combined with 780-900cm -1 The area integration results of the DME Raman spectrum peaks and the NMR data show that the structure of the magnesium ion in the electrolyte of Example 3 is [Mg(DME) 2.5 OTf] + .
[0097] Combining NRM and Raman, it can be seen that the solvation structure of magnesium ions in the electrolyte of Example 1 is [Mg(DME)3] 2+ , the solvation structure of magnesium ions in the electrolyte of Example 3 is [Mg(DME) 2.5 OTf] + .
[0098] It can be proved that when the electrolyte organic magnesium salt is dissolved in an ether solvent, the organic magnesium salt will be dissociated into magnesium cations complexed with the solvent [Mg(solvent) x ] 2+ and anionic BHFIP - , the anions in the additive participate in the solvation structure of magnesium ions, changing the solvation structure of magnesium ions from [Mg(solvent) x ] 2+ becomes [Mg(solvent) m (anion) n ] + .
[0099] Conductivity test
[0100] The electrolytes obtained in Examples 1-8 were tested using a Mettler Toledo conductivity tester.
[0101] The electrolyte conductivity in Example 1 was measured to be 11.2 mS / cm, the electrolyte conductivity in Example 2 was 12.4 mS / cm, the electrolyte conductivity in Example 3 was 13.3 mS / cm, the electrolyte conductivity in Example 4 was measured to be 10.9 mS / cm, the electrolyte conductivity in Example 5 was 11.5 mS / cm, the electrolyte conductivity in Example 6 was 11.7 mS / cm, and the electrolyte conductivity in Example 7 was 11.5 mS / cm. The electrolyte conductivity in Example 8 is 12.3 mS / cm, the electrolyte conductivity in Example 9 is 12.6 mS / cm, the electrolyte conductivity in Example 10 is 10.5 mS / cm, the electrolyte conductivity in Example 11 is 8.6 mS / cm, the electrolyte conductivity in Example 12 is measured to be 13.4 mS / cm, the electrolyte conductivity in Example 13 is 11.7 mS / cm, and the electrolyte conductivity in Example 14 is 13.7 mS / cm.
[0102] It can be seen from the above that the addition of an appropriate concentration of NaOTf additive can improve the conductivity of the magnesium ion electrolyte, but too high an additive concentration will reduce the conductivity. The conductivity of the electrolyte of the present invention exceeds 8mS / cm, and when the concentration of the solute magnesium salt is 0.3mol / L, the conductivity of the electrolyte exceeds 10mS / cm, which can prove that the electrolyte of the present invention has high ionic conductivity.
[0103] Electrochemical Window Test
[0104] [Battery assembly]
[0105] Copper foil, aluminum foil or stainless steel was used as the working electrode, metal magnesium was used as the counter electrode and reference electrode, and a glass fiber membrane was used as a separator. 80 μL of the electrolyte obtained in Examples 1-4 was added respectively to assemble a button cell.
[0106] [test]
[0107] The electrochemical window test was performed using a Biologic VMP3 electrochemical workstation with a scan rate of 5 mV / s. Figure 3 , Figure 4 , Figure 5 and Figure 6 As shown, for the working electrode copper foil, the anodic oxidation potential of the electrolyte in Example 1 was measured to be about 2.8 V vs. Mg / Mg 2+ After adding the additive (Examples 2, 3, and 4), the anodic oxidation potential of the electrolyte exceeded 3.0 V vs. Mg / Mg 2+ ,, especially in Example 3, the electrolyte can reach 3.2V vs.Mg / Mg 2+ The above shows that the electrolyte of the present invention has a wide electrochemical stability window.
[0108] Magnesium deposition-dissolution performance test
[0109] [Battery assembly]
[0110] A symmetrical magnesium||magnesium battery was assembled, using a glass fiber membrane as a separator, and 80 μL of the electrolyte obtained in Example 3 was added.
[0111] [test]
[0112] 0.1~2mA cm -2 The magnesium deposition-dissolution performance test was carried out under the current density of , and the deposition-dissolution results were as follows Figure 7 As shown, at 0.1, 0.2, 0.5, 1.0, 2.0 mA cm -2 The polarization of the battery under the current density is relatively small, and there is no obvious increase in polarization, showing excellent reversible magnesium deposition characteristics, indicating that the electrolyte of the present invention can carry out stable magnesium ion transport.
[0113] The above tests can prove that the present invention successfully prepares an electrolyte for use in magnesium ion batteries, and the electrolyte has a wide electrochemical stability window, high ionic conductivity, excellent reversible magnesium deposition characteristics, and excellent intrinsic performance.
[0114] AC impedance test
[0115] [Battery assembly]
[0116] Positive electrode preparation: The positive electrode active material copper selenide, the conductive agent acetylene black, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of N-methylpyrrolidone solvent at a mass ratio of 6:3:1 to form a uniform slurry. The slurry is coated on the current collector copper foil, and after vacuum drying at 80°C, it is cut into positive electrode sheets with a diameter of 11 mm.
[0117] Assembling a button cell: using the prepared positive electrode sheet as the working electrode, metal magnesium as the counter electrode and the reference electrode, and a glass fiber membrane as a separator, adding 80 μL of the electrolyte obtained in Examples 1 and 3, and assembling a button cell.
[0118] [test]
[0119] The charge and discharge tests were carried out using a Biologic VMP3 electrochemical workstation.
[0120] like Figure 8As shown, the copper selenide positive electrode has a smaller impedance in the electrolyte of Example 3 than in Example 1, and the value is only about 40%, indicating that the copper selenide positive electrode has a faster charge transfer in Example 3, which is mainly due to the special magnesium ion solvation structure in the electrolyte of Example 3. Its rapid desolvation process is the main reason for the superior high current performance of the copper selenide positive electrode in the electrolyte of Example 3.
[0121] Therefore, it can be directly proved that the electrolyte of the present invention has a rapid desolvation process, thereby greatly improving the magnesium ion storage performance of the positive electrode material under high current.
[0122] Charge and discharge test
[0123] [Battery assembly]
[0124] Positive electrode preparation: The positive electrode active material copper selenide, the conductive agent acetylene black, and the binder polyvinylidene fluoride are fully stirred and mixed in a proper amount of N-methylpyrrolidone solvent in a mass ratio of 6:3:1 to form a uniform slurry. The slurry is coated on the current collector copper foil, and after vacuum drying at 80°C, it is cut into positive electrode sheets with a diameter of 11 mm.
[0125] Assembling a button cell: using the prepared positive electrode sheet as the working electrode, metal magnesium as the counter electrode and the reference electrode, and a glass fiber membrane as a separator, adding 80 μL of the electrolyte obtained in Examples 1 and 3, and assembling a button cell.
[0126] [test]
[0127] The charge and discharge tests were carried out using a Xinwei electrochemical workstation.
[0128] like Fig. 9 As shown, the first-cycle discharge capacity of the copper selenide positive electrode at a current density of 100mA / g in the electrolyte of Example 1 is 58mAh / g. After 60 cycles of charge and discharge activation, the copper selenide positive electrode reached a maximum discharge capacity of 228mAh / g (61% of the theoretical capacity). In the electrolyte of Example 3, the first-cycle discharge capacity of the copper selenide positive electrode is 170mAh / g, and after 40 cycles of activation, it reaches a maximum capacity of 357mAh / g (95% of the theoretical capacity). This indicates that the copper selenide positive electrode has a higher first-cycle discharge capacity, a shorter number of activation cycles, and a higher reversible discharge capacity in the electrolyte of Example 3 containing additives.
[0129] At the same time, if Fig.10As shown, when the current density is further increased to 200, 500, and 1000 mAh / g, the discharge specific capacity of the copper selenide positive electrode is 193 / 304, 150 / 277, and 117 / 246 mAh / g in Example 1 and Example 3. As the current density increases, the effect of the additive on the capacity of the copper selenide positive electrode becomes more obvious, especially at a high current of 1000 mA / g, the reversible discharge specific capacity of the copper selenide positive electrode is increased by more than twice.
[0130] Through the charge and discharge test, it can be known that when the electrolyte of the present invention is applied to the magnesium ion battery, the positive electrode material has a high reversible discharge specific capacity each time during the cycle under a large current, which can further prove from the side that the electrolyte of the present invention has a rapid desolvation process, thereby greatly improving the magnesium ion storage performance of the positive electrode material under a large current.
[0131] Combined with the above tests, it can be seen that the electrolyte prepared by the present invention for use in magnesium ion batteries has a wide electrochemical stability window, high ionic conductivity, excellent reversible magnesium deposition characteristics and a rapid desolvation process, and the intrinsic performance of the electrolyte is excellent.
[0132] The electrolyte of the present invention has a special magnesium ion solvation structure, and the anion additive enters the magnesium ion solvation structure, making the magnesium ion desolvation process easier, which solves the key problem of the rapid attenuation of the discharge specific capacity of the positive electrode material under high current.
[0133] The electrolyte of the present invention is friendly to conversion reaction type positive electrode materials. The maximum discharge specific capacity released by the positive electrode material in the electrolyte of the present invention is greatly improved, and at a larger current, the improvement of the discharge specific capacity of the positive electrode material is more prominent.
[0134] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. An electrolyte for magnesium ion battery, characterized in that: It comprises a solute, a solvent and an additive; wherein the solute comprises magnesium hexafluoroisopropoxyborate, the additive comprises an ionic compound whose anion is different from the anion in the solute, and the solvent comprises an organic ether solvent; The additive includes an ionic compound whose anion is trifluoromethanesulfonate, hexafluorophosphate, bistrifluoromethanesulfonyl imide, bisfluorosulfonyl imide or perchlorate; the concentration of the additive is 0.05-0.5 mol / L; The organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
2. The electrolyte for magnesium ion battery according to claim 1, characterized in that: In the electrolyte, the concentration of magnesium hexafluoroisopropoxyborate is 0.05-0.5 mol / L.
3. A method for preparing an electrolyte for magnesium ion battery according to any one of claims 1 to 2, characterized in that: The following steps are involved: Dispersing magnesium borohydride in a first organic ether solvent to obtain a magnesium borohydride dispersion, adding hexafluoroisopropanol to the magnesium borohydride dispersion under stirring conditions, and reacting under the protection of an inert atmosphere to obtain a mixed solution after the reaction is completed; Under the protection of an inert atmosphere, the mixed solution is filtered, and the filtrate is vacuum-treated to remove the solvent to obtain magnesium hexafluoroisopropoxyborate; Continuing under the protection of an inert atmosphere, magnesium hexafluoroisopropoxyborate and an additive are dissolved in a second organic ether solvent to obtain the desired electrolyte; wherein the additive is an ionic compound whose anion is different from the anion in the solute.
4. The preparation method according to claim 3, characterized in that: The concentration of the magnesium borohydride dispersion is 10-50 g / L.
5. The preparation method according to claim 3, characterized in that: The molar ratio of magnesium hexafluoroisopropoxyborate to the additive is 3:(1-5).
6. The preparation method according to claim 3, characterized in that: The first organic ether solvent comprises a mixture of one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran and 2-methyltetrahydrofuran; The second organic ether solvent comprises a mixture of one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
7. A magnesium ion battery, characterized in that: The electrolyte is the electrolyte used for magnesium ion batteries as described in any one of claims 1 to 2.
Citation Information
Patent Citations
Negative electrode for magnesium secondary battery, method for producing same, and magnesium secondary battery
CN109075326A
Electrolytic solution and electrochemical device
CN112534621A
Method for manufacturing boron based magnesium salt, method for manufacturing electrolyte solution, boron based magnesium salt, electrolyte solution and secondary battery
JP2021178801A